Model of Government Communication to Build Leadership Credibility in Banten Province, Indonesia - Eva Eviany; Astika Ummy Athahirah (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
Credibility is a significant aspect of leadership practice that causes followers to respect a leader voluntarily. Government credibility is determined through communication between the government and its people. However, the credibility of the government leadership in Banten Province is a challenge, considering that Banten Province is one of the regions with political dynasties. Therefore, this study describes the function of communication and formulates a communication function model to build the credibility of Banten Province's government leadership. This study used Quasi-Qualitative Design (QQD) with collection through semi-structured interviews, observations, documentation, and questionnaires. We show the implementation of two government communication functions, such as influencing and conveying policies. While the other two parts, namely educating and entertaining, need to be maximised. Meanwhile, the dimensions of leadership credibility, such as integrity, competence, and leadership, have gone well. The government communication model is developed from the Schramm communication model in a circular form to build leadership credibility in Banten Province. In leadership studies, this model can guide increasing credibility, so all formal and informal leadership organisations can adopt this model by formulating leadership-related empirical facts and various references. It is highly applicable to leadership 4.0